Regulation of Banana Phytoene Synthase (MaPSY) Expression, Characterization and Their Modulation under Various Abiotic Stress Conditions - Kaur, Navneet; Pandey, Ashutosh; Shivani,; Kumar, Prateek; Pandey, Pankaj; Kesarwani, Atul K.; Mantri, Shrikant S.; Awasthi, Praveen; Tiwari, Siddharth (Frontiers in Plant Science, 2017)
Phytoene synthase (PSY) is a key regulatory enzyme of carotenoid biosynthesis pathway in plants. The present study examines the role of PSY in carotenogenesis and stress management in banana. Germplasm screening of ten Indian cultivars showed that Nendran (3011.94 μg/100g dry weight) and Rasthali (105.35 μg/100g dry weight) contained the highest and lowest amounts of β-carotene, respectively in ripe fruit-pulp. Nendran ripe pulp also showed significantly higher antioxidant activity as compared to Rasthali. Meta-analysis of three banana PSY genes (MaPSY1, MaPSY2, and MaPSY3) was performed to identify their structural features, subcellular, and chromosomal localization in banana genome. The distinct expression patterns of MaPSY1, MaPSY2, and MaPSY3 genes were observed in various tissues, and fruit developmental stages of these two contrasting cultivars, suggesting differential regulation of the banana PSY genes. A positive correlation was observed between the expression of MaPSY1 and β-carotene accumulation in the ripe fruit-peel and pulp of Nendran. The presence of stress responsive cis-regulatory motifs in promoter region of MaPSY genes were correlated with the expression pattern during various stress (abscisic acid, methyl jasmonate, salicylic acid and dark) treatments. The positive modulation of MaPSY1 noticed under abiotic stresses suggested its role in plant physiological functions and defence response. The amino acid sequence analysis of the PSY proteins in contrasting cultivars revealed that all PSY comprises conserved domains related to enzyme activity. Bacterial complementation assay has validated the functional activity of six PSY proteins and among them PSY1 of Nendran (Nen-PSY1) gave the highest activity. These data provide new insights into the regulation of PSY expression in banana by developmental and stress related signals that can be explored in the banana improvement programs.